Pengaruh Atmosphere, Kualitas Pelayanan Dan Lokasi Strategis Terhadap Kepuasan Pelanggan Pada Konsumen Depot Tanjung Api Malang - Muthoharoh, Aisah; Wahono, Budi; Paramadina, Dita Roosemella (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The objective of this study was to investigate and measure the impact of the atmosphere, service quality, and strategic location on customer satisfaction at Tanjung Api Depot Malang. The research employs a quantitative approach. Sampling was conducted among Tanjung Api Depot Malang customers using the Malhotra formula, resulting in a sample size of 75 respondents. This study utilizes multiple linear regression analysis with SPSS 22 as the analytical tool. The F-test and t-test were used to test hypotheses. The study's findings show that Tanjung Api Depot Malang's customer satisfaction is significantly impacted by the atmosphere, service quality, and strategic location all at once. At Tanjung Api Depot in Malang, the factors of atmosphere and strategic location have a major impact on customer satisfaction. Meanwhile, the Service Quality variable does not have a significant partial effect on Customer Satisfaction at Tanjung Api Depot Malang. Keywords: Atmosphere, Service Quality, Strategic Location and Customer Satisfaction